The Book of Inkscape, 2nd Edition - Kirsanov, Dmitry (No Starch Press, 2021)
Dmitry Kirsanov, a former core Inkscape developer, shares his knowledge of Inkscape's inner workings as he shows how to use Inkscape to draw with various tools, work with objects, apply realistic and artistic effects, and more. Step-by-step task-based tutorials show you how to create business cards, animations, technical and artistic drawings, and graphic assets for games. This second edition covers the new tools, improved text features, advanced new path effects and filters, as well as many new UI conveniences in Inkscape 1.0. A new chapter describes Inkscape's extensions for both users and developers.